1969
DOI: 10.4141/cjss69-014
|View full text |Cite
|
Sign up to set email alerts
|

Free Amino Acid Composition of the Plant Root Environment Under Field Conditions

Abstract: The free amino acids and the total ninhydrin-reacting material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…In the case of mineral nutrients, their concentrations fluctuate with season and this has been attributed to fluctuations of microbial activity which are themselves in turn influenced by changes of climatic factors (Gupta & Sowden & Ivarson (1966); 2, Ivarson & Sowden (1969);3, Read & Bajwa (1985); 4, Present study.…”
Section: A Comparison Of the Results Obtained By Hplc And Ninhydrinmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of mineral nutrients, their concentrations fluctuate with season and this has been attributed to fluctuations of microbial activity which are themselves in turn influenced by changes of climatic factors (Gupta & Sowden & Ivarson (1966); 2, Ivarson & Sowden (1969);3, Read & Bajwa (1985); 4, Present study.…”
Section: A Comparison Of the Results Obtained By Hplc And Ninhydrinmentioning
confidence: 99%
“…A number of workers have indicated that non-amino acid compounds can be included in ninhydrin assays. Thus, the ninhydrin method was found by Ivarson & Sowden (1969) to give slightly higher values than did the Technicon amino-acid auto-analyser. They reported that the ratios of the ninhydrin to the autoanalyser method varied from 10 to 1'4.…”
Section: Quantitative Analysis Of Individual Amino Acids By Hplcmentioning
confidence: 99%
“…(See Saxby, 1969;Spakhov and Spakhova, 1970;Greaves and Wilson, 1969;Kowalenko and McKercher, 1971;Ivarson and Sowden, 1969;and Kononova, 1966, for more complete discussions of the organic compounds in soils. )…”
Section: Organic Chemistry Of Lead In Natural Water Systemsmentioning
confidence: 99%
“…Recently, in their studies using a non-sterile environment, Ivarson and Sowden (8) showed that under field conditions larger quantities of amino acids are found in the rhizosphere than in the non-rhizosphere. That study led to the present experiment which was designed to investigate the effect of growth stage, fertility and soil temperature on the amino acids of the rhizosphere as found under conditions approachinlg those of the natural environment.…”
Section: Introductionmentioning
confidence: 99%